Preparing for Debt Management in Ulaanbaatar : Issues to Consider - World Bank (Washington, DC, 2014)
This note is part of a broader technical assistance program designed to assist the City of Ulaanbaatar (UB) to improve its financial management system, assess the quality of municipal services provision, and mobilize resources from the capital markets to fund urban infrastructure. This note identifies key issues for UB to consider when putting in place an effective debt management framework prior to acquiring debt. It goes hand-in-hand with a separate "Financial Self-Assessment" that was carried out in preparation for a credit rating.